Constraining the age of the Mitu Group, South-East Peru: U-Pb ages of detrital and igneous zircons - Reitsma, Mariël Jel (2010)
Trabajo presentado en el European Geophysical Union, General Assembly 2010, del 2-7 de mayo, 2010, en Vienna, Austria.